USING METACOGNITIVE STRATEGIES IN TEACHING LISTENING TO EXPLANATION TEXT - nor, hidayah (English Department of Faculty of Tarbiyah and Teacher Training, 2016)
Listening is receptive skill and it is very important skill in foreign language classrooms because it provides input for the learners; by listening the students can produce language such as speaking and writing by vocabulary that they obtain from listening. Listening process has both top-down listening process that involves activation of schematic knowledge and contextual knowledge and bottom-up listening process involves prior knowledge of the language system such as phonology, grammar, and vocabulary. Metacognitive strategies is one of language learning strategies in teaching English and considered as the most essential ones in developing learners? skills (Anderson, 1991). It is also help the students to make language learning more successful, self-directed, and enjoyable (Oxford: 1989, p. 235). Metacognitive consists of planning for learning, thinking about the learning process as it is taking place, monitoring of one's production or comprehension, and evaluating learning after an activity is completed. This study is intended to use metacognitive strategies in teaching listening and to provide English lecturers with interesting and effective teaching strategies in enhancing the students? active participation in teaching and learning process and improving students? listening ability. The students use metacognitive strategies to improve their ability in listening. This study will also give additional value to the effort of increasing the quality of teaching English particularly listening in Indonesia.